Detection and imaging of Hg(II) in vivo using glutathione-functionalized gold nanoparticles - Li, Gufeng; Li, Shaoqing; Wang, Rui; Yang, Min; Zhang, Lizhu; Zhang, Yanli; Yang, Wenrong; Wang, Hongbin (Beilstein Journal of Nanotechnology, 2022)
The optical and biological properties of functionalized gold nanoparticles (GNPs) have been widely used in sensing applications. GNPs have a strong binding ability to thiol groups. Furthermore, thiols are used to bind functional molecules, which can then be used, for example, to detect metal ions in solution. Herein, we describe 13 nm GNPs functionalized by glutathione (GSH) and conjugated with a rhodamine 6G derivative (Rh6G2), which can be used to detect Hg(II) in cells. The detection of Hg2+ ions is based on an ion-catalyzed hydrolysis of the spirolactam ring of Rh6G2, leading to a significant change in the fluorescence of GNPs-GSH-Rh6G2 from an “OFF” to an “ON” state. This strategy is an effective tool to detect Hg2+ ions. In cytotoxicity experiments, GNPs-GSH-Rh6G2 could penetrate living cells and detect mercury ions through the fluorescent “ON” form.
Keywords: cell imaging; fluorescence probes; glutathione; gold nanoparticles; mercury ions; rhodamine 6G derivatives